Ammonium removal from high-strength aqueous solutions by Australian zeolite. Issue 8 (2nd July 2016) - Wijesinghe, D. Thushari N.; Dassanayake, Kithsiri B.; Sommer, Sven G.; Jayasinghe, Guttila Y.; J. Scales, Peter; Chen, Deli
ABSTRACT: Removal of ammonium nitrogen (NH4 + -N) particularly from sources which are highly rich in nitrogen is important for addressing environmental pollution. Zeolites, aluminosilicate minerals, are commonly used as commercial adsorbents and ion-exchange medium in number of commercial applications due to its high adsorption capacity of ammonium (NH4 + ). However, detailed investigations on NH4 + adsorption and ion exchange capacities of Australian natural zeolites are rare, particularly under higher NH4 + concentrations in the medium. Therefore, this study was conducted to determine NH4 + adsorption characteristics of Australian natural zeolites at high NH4 + concentrations with and without other chemical compounds in an aqueous solution. Results showed that initial NH4 + concentration, temperature, reaction time, and pH of the solution had significant effects on NH4 + adsorption capacity of zeolite. Increased retention time and temperature generally had a positive impact on adsorption. Freundlich model fitted well with adsorption process of Australian natural zeolites; however, Langmuir model had best fitted for the adsorption process of sodium (Na + ) treated zeolites. NaCl treatment increased the NH4 + adsorption capacity of Australian zeolites by 25% at 1000 mg-N, NH4 + solution. The maximum adsorption capacity of both natural Australian zeolites and Na + treated zeolites were estimated as 9.48 and 11.83 mg-N/g, respectively, which is lower than many zeolites from other sources. Compared to the NH4 + only medium, presence of other competitive ions and acetic acid in the medium (resembling composition in digested swine manure slurries) reduced NH4 + removal of natural and Na + treated zeolites by 44% and 57%, respectively. This suggests detailed investigations are required to determine practically achievable NH4 + -N removal potential of zeolites for applications in complex mediums such as animal manure slurries.